PENERAPAN PERANGKAT MAGGOT KOMPOSTING MODULAR DI SEKITAR KAMPUNG ILMU DESA CISARUA PURWAKARTA - Darajat, Teddy Mohamad; Ranudinata, Hari Nugraha; Kalbuadi, Gandung Anugrah; Sugianto, Donna Angelina (LPPM Universitas Sangga Buana, 2025)
The problem faced by the residents of Kampung Ilmu Purwakarta is their dependence on relatively expensive commercial animal feed. This causes high livestock production costs and a lack of utilisation of organic waste as a resource of economic value. To overcome these problems, Community Service (PKM) activities are carried out to improve the financial welfare of residents through maggot cultivation as an alternative source of quality animal feed, while optimising the utilisation of organic waste into organic fertiliser. The partners in this activity are 4 families who have poultry businesses living around Kampung Ilmu Purwakarta. The implementation method consists of several stages, namely an initial survey to evaluate the socio-economic conditions and potential of residents' livestock, technical counselling on sustainable maggot cultivation, assistance in making media and cultivation tools, and offline and online monitoring after training. The results of the activity showed that maggots can be harvested within 2-3 weeks after maintenance and used directly as an alternative animal feed. By using maggots, residents managed to reduce commercial feed costs by around 40%. Post-activity monitoring proved that all partners were able to carry out the maggot cultivation cycle independently. This activity has a positive impact in the form of increasing the independence of residents in providing cheap and environmentally friendly animal feed, as well as a real contribution to the management of organic waste productively. These results indicate that maggot cultivation has great potential to be developed more widely as an economic and environmental solution at the local community level.